ATP-dependent motor activity of the transcription termination factor Rho from Mycobacterium tuberculosis. Issue 12 (20th May 2015) - D'Heygère, François; Schwartz, Annie; Coste, Franck; Castaing, Bertrand; Boudvillain, Marc
Abstract: The bacterial transcription termination factor Rho—a ring-shaped molecular motor displaying directional, ATP-dependent RNA helicase/translocase activity—is an interesting therapeutic target. Recently, Rho from Mycobacterium tuberculosis (Mtb Rho) has been proposed to operate by a mechanism uncoupled from molecular motor action, suggesting that the manner used by Rho to dissociate transcriptional complexes is not conserved throughout the bacterial kingdom. Here, however, we demonstrate that Mtb Rho is a bona fide molecular motor and directional helicase which requires a catalytic site competent for ATP hydrolysis to disrupt RNA duplexes or transcription elongation complexes. Moreover, we show that idiosyncratic features of the Mtb Rho enzyme are conferred by a large, hydrophilic insertion in its N-terminal 'RNA binding' domain and by a non-canonical R-loop residue in its C-terminal 'motor' domain. We also show that the 'motor' domain of Mtb Rho has a low apparent affinity for the Rho inhibitor bicyclomycin, thereby contributing to explain why M. tuberculosis is resistant to this drug. Overall, our findings support that, in spite of adjustments of the Rho motor to specific traits of its hosting bacterium, the basic principles of Rho action are conserved across species and could thus constitute pertinent screening criteria in high-throughput searches of new Rho inhibitors.